PENGUJIAN EFISIENSI PASAR DAN TINGKAT KONVERGENSI HARGA KOMODITAS KOPI ARABIKA DAN KOPI ROBUSTA (Studi Kasus pada Pasar Komoditas Berjangka di Indonesia) - Dewi Pertiwi (Institute of Research and Community Outreach - Petra Christian University, 2015)
This purpose of this paper is to test the market efficiency and the level of price convergence in the Arabica coffee and Robusta coffee commodity markets, which traded on the Jakarta Futures Exchange (JFX). Unit root test such as Augmented Dickey-Fuller (ADF) and Philip-Perron (PP) evidence that futures and spot prices are stasionary. Johansen Cointegration Test and Error Correction Model (ECM) provide that the Arabica coffee and Robusta coffee commodity markets in Indonesia is an efficient market and contain the risk premium. The result indicate that the Arabica coffee and Robusta coffee commodity markets has a high level of price convergence. The implication, market participants or investors still choose to do hedging activities because the utility of futures contracts as a hedge has been effective.